PENILAIAN PENERAPAN TATA KELOLA PERUSAHAAN DI INDONESIA DAN PENGARUHNYA TERHADAP KINERJA KEUANGAN - Dienda Amalia Desmawardani; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
The purposive of this research is to examine impact of corporate governance implementation rating on financial performance in Indonesia. The independent variables is corporate governance implementation rating while the dependent variables are financial performance, firm value, dan company growth. The Control variables are company size, company age, listing ago,and  leverage.This research uses panel data regression analysis method use EViews with secondary data obtained by purposive sampling method. Research data is secondary data from Corporate Governance Perception Index’s data and annual reports that listed on the Indonesia Stock Exchange in 2012-2017. The results of this reasearch is indicate a significant influence between corporate governance implementation rating on financial performance and firm value. But, there is not significant influence between corporate governance implementation rating on company growth.